The Plague (Black Death) Is Still Around and May Come Back - Nader Aghakhani; Shahin Izadi; Kazhal Mobaraki; Jamal Ahmadzadeh; Arash Aliasghari (Shahrekord University of Medical Sciences, 2022)
Plague has been among the most devastating infectious diseases in human history. The decrease in the plague in recently reported cases and studies implies that the plague should not recur, but the fact is that it (Black Death) is still around and may appear again. The disease can be occult for many years. The reemergence of the plague epidemic with unusual clinical form, magnitude, and rapid expansion at any place and time without prior notice could pose a serious risk to public health. Plague outbreaks most likely result from the reactivation of organisms in local foci. The reemergence of foci suggests that environmental or climatic changes could be favorable for an epidemiological cycle of Yersinia pestis. Thus, countries harboring plague foci can be at risk of outbreaks in the future. Different epidemiological aspects of the plague must be emphasized in prophylactic medical plans and health education systems, and healthcare workers should be alert and aware of the natural cycle, as well as clinical symptoms and signs of plague. Finally, surveillance, education, and research are also suggested regarding this fatal infection and other emerging diseases.